Pidana Mati Bersyarat: Pergeseran Filosofi Pemidanaan Dari Retributif Ke Rehabilitatif Dalam KUHP Nasional - Aditia, Fanita; Setiawan, Beni; Kusuma Sumantri, Aditya; Ambron Ritonga, Wildan (Faculty of Law, Universitas Jambi, 2026)
Law Number 1 of 2023 concerning the Criminal Code introduced the concept of conditional death penalty as a radical innovation in the Indonesian penal system. This study aims to analyze the normative construction of conditional death penalty as a manifestation of the shift in the paradigm of punishment from a retributive to a rehabilitative orientation. The research method used is normative legal research with a legislative, conceptual, and philosophical approach. Primary legal materials include the National Criminal Code and related laws and regulations, while secondary legal materials include doctrine, punishment theory, and relevant scientific literature. This study reveals that conditional death penalty is the result of a dialectical synthesis between the retributive and rehabilitative paradigms that produces a fundamental philosophical paradox. The main findings of the study indicate: First, the construction of conditional death penalty creates an ambiguous ontological status for convicts—